Training Development and Implementation of Digital Learning for Lecturers at Poltekkes Kemenkes Kendari - Eko Risdianto; Kartini Kartini; Hikmandayani Hikmandayani; Farming Farming (CV Media Inti Teknologi, 2024)
This training aims to provide understanding to Kendari Ministry of Health Polytechnic Lecturers regarding the development and implementation of digital learning. Training was held on 4-5 June 2024 with a total of 17 training participants. After the training activity ends, an evaluation is carried out by asking the training participants to fill out a Google Form containing statements related to the participant's response to the training activity. Google Forms are structured as a closed questionnaire with 4 answer choices. Student responses regarding training activities were analyzed on the data obtained in the form of percentages. Percentages were obtained based on modified Likert Scale calculations. Each item in the instrument is given a quantitative value, namely 4 for the Strongly Agree category, 3 for the Agree category, 2 for the Disagree category, and 1 for the Agree category. Based on the evaluation results, it is known that the training was carried out well and the training participants gained an understanding of the development & implementation of digital learning as one of the right choices to use in the digital era.